Perancangan Interior Omah Kucing di Surabaya - Jenniffer Magdalena; Purnama Esa Dora Tejokeosumo; Anik Rakhmawati (Intra, 2019)
The growing population of cats in Surabaya and throughout Indonesia, has the potential to spread zoonotic diseases (transmitted from human to animal or vice versa). Based on the above problems, the design of a cat center for wild cats named Omah Kucing which will consist of cat shelter, cat clinic, and cat café. The design method used is the method of design thinking. The results of this design is, a place called “Omah Kucing” with the concept of a whimsical house which means a unique and strange house where the author will apply a fun and playful theme where design can enhance interaction between cats and humans so that visitors can be interested and know more again about the characteristics and uniqueness of cats.